Prinsip Epistemologi Makrifat dalam Tasawuf Bagi Penguatan Karakter - Nunu Burhanuddin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
This paper elaborates the concept of knowledge according to the Sufis through the concept of makrifat, which is hierarchically achieved through a process of soul purification (tazkiyah al-nafs). From this process is born awareness of the oneness of Allah, the Most Absolute, which involves the potential of the senses and reason. The research in this article uses the literature study method of Sufism written by Sufis, especially when discussing the subject of makrifat. Such as the works of Rasâil al-Junaid by Al-Junaid al-Baghdadi, Ihya 'Ulum al-Din by Abu Hâmid al-Ghazali, and Kitab al-Zuhud by Ahmad bin Hanbal. The results showed that there are epistemological principles in the science of Sufism (makrifat) that can lead to the acquisition of rational knowledge that is integrated with righteous deeds and the formation of character. These epistemological principles are in the form of liberation of ego, superego, and lust, principles of piety and sincerity, principles of faith that guarantee the functionalization of reason, and principles of revelation that ratify empirical, rational, and intuitive knowledge. These epistemological principles are seen as relevant for the creation of character education and complete human action. Tulisan ini mengelaborasi konsep pengetahuan menurut para sufi melalui konsep makrifat, yang secara hirarkis dicapai melalui proses penyucian jiwa (tazkiyah al-nafs). Dari proses ini lahirlah kesadaran akan keesaan Allah Yang Maha Absolut yang melibatkan potensi inderawi dan rasio. Penelitian dalam artikel ini menggunakan metode studi kepustakaan atas karya-karya tasawuf yang ditulis oleh para sufi, khususnya ketika membahas perihal makrifat. Seperti karya Rasâil al-Junaid oleh Al-Junaid al-Baghdadi, Ihya ‘Ulum al-Din oleh Abu Hâmid al-Ghazali, dan Kitab al-Zuhud oleh Ahmad bin Hanbal. Hasil penelitian menunjukkan bahwa terdapat prinsip-prinsip epistemologi dalam ilmu tasawuf (makrifat) yang dapat mengantarkan kepada perolehan pengetahuan rasional yang terintegrasi dengan amal saleh dan terbentuknya karakter. Prinsip-prinsip epistemologis tersebut berupa pembebasan ego, super ego dan hawa nafsu, prinsip kesalehan dan kesungguhan, prinsip iman yang menjamin fungsionalisasi akal, serta prinsip kewahyuan yang meratifikasi pengetahuan empiris, rasional dan intuitif. Prinsip-prinsip epistemologis ini dipandang relevan bagi terciptanya pendidikan berkarakter dan tindakan paripurna manusia.